2003
DOI: 10.1126/science.1081203
|View full text |Cite
|
Sign up to set email alerts
|

Axons Guided by Insulin Receptor in Drosophila Visual System

Abstract: Insulin receptors are abundant in the central nervous system, but their roles remain elusive. Here we show that the insulin receptor functions in axon guidance. The Drosophila insulin receptor (DInR) is required for photoreceptor-cell (R-cell) axons to find their way from the retina to the brain during development of the visual system. DInR functions as a guidance receptor for the adapter protein Dock/Nck. This function is independent of Chico, the Drosophila insulin receptor substrate (IRS) homolog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
126
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 137 publications
(132 citation statements)
references
References 25 publications
6
126
0
Order By: Relevance
“…DILP release from the DILP2 neurons may thus be modulated by intracellular Ca 2ϩ signaling and function in the process of dendritic outgrowth during the pupal stages. In Drosophila, insulin signaling contributes to guidance of photoreceptor cell axons from the retina to the brain during development of the visual system (Song et al, 2003). Insulin transport into the CNS appears to increase in the neonatal period (Banks, 2004) in mammalian systems, suggesting that peripheral insulin levels influence the formation of circuits in the developing brain (Needleman and McAllister, 2008).…”
Section: Intracellular Calcium Homeostasis In Dilp2 Neurons and The Cmentioning
confidence: 99%
“…DILP release from the DILP2 neurons may thus be modulated by intracellular Ca 2ϩ signaling and function in the process of dendritic outgrowth during the pupal stages. In Drosophila, insulin signaling contributes to guidance of photoreceptor cell axons from the retina to the brain during development of the visual system (Song et al, 2003). Insulin transport into the CNS appears to increase in the neonatal period (Banks, 2004) in mammalian systems, suggesting that peripheral insulin levels influence the formation of circuits in the developing brain (Needleman and McAllister, 2008).…”
Section: Intracellular Calcium Homeostasis In Dilp2 Neurons and The Cmentioning
confidence: 99%
“…The IR regulates neuronal survival in C. elegans (9). In Drosophila, the IR serves an important function to guide retinal photoreceptor axons from the retina to the brain during development (10), and the IR influences the size and number of photoreceptors (11). The lack of IR activation leads to neurodegeneration in brain/neuron-specific IR knock-out mice (12).…”
Section: Insulin Receptor (Ir)mentioning
confidence: 99%
“…[1][2][3][4] However, excessive insulin signaling caused by hyperinsulinemia or overexpression of insulin receptor (IR) has been linked to cancer progression. 5 Recent epidemiological and experimental studies have demonstrated that hyperinsulinemia is a major cancer risk factor among many type 2 diabetes mellitus patients and obese individuals.…”
Section: Introductionmentioning
confidence: 99%